Navigating the Challenges of Digital Transformation in Traditional Organization - Maratis, Jerry; Ramadan, Ahmad; Rahmania Az Zahra, Achani; Ahsanitaqwim, Ridhuan; Bennet, Daniel (APTISI Transactions on Management (ATM), 2024)
Digital transformation has become a critical strategy for traditional organiza- tions to maintain competitiveness in an increasingly technology-driven market. Technologies such as fintech, blockchain, artificial intelligence (AI), and cloud computing have significantly reshaped operational efficiency and customer en- gagement within these organizations. However, traditional organizations, characterized by their legacy systems and hierarchical structures, encounter various challenges in adopting these technologies. This study primarily aims to explore the key barriers that hinder digital transformation in traditional organizations and to propose effective strategies for overcoming these challenges. Utilizing a comprehensive literature review from 2018 to 2023, this research examines key studies on digital transformation in traditional business contexts. The find- ings reveal major challenges, including organizational inertia, skills gaps, de- pendency on outdated systems, and leadership deficiencies. To address these barriers, the study proposes strategies such as leadership development, work- force retraining, and investment in modern digital infrastructure. The results suggest that successful digital transformation requires a multifaceted approach, aligning technological adoption with organizational culture and sustainability goals. This research provides valuable insights for traditional organizations nav- igating the complexities of digital transformation.